PROSES KOGNITIF KREATIF MAHASISWA TINGKAT I DALAM BELAJAR KEWARGANEGARAAN MELALUI PEMBELAJARAN KONSTRUKTIF KONTEKSTUAL SECARA VIRTUAL - Dewi, Dinie Anggraeni; Nur’aeni, Nani (Universitas Tanjungpura, 2022)
This study aims to find a description of the creative cognitive process abilities of students in learning citizenship, through virtual contextual constructive learning. The research uses a qualitative approach with classroom action research methods, based on online learning via whatsapp, zoom meeting/google meet and google classroom. The research subjects were first semester students at the Faculty of Teacher Training and Education, Universitas Islam Nusantara who took Citizenship Education courses. The research method used is action research with a practical action research model / classroom action research. The indicators for measuring creative cognitive processes include: the ability to identify, formulate problems and create hypotheses to solve problems, the ability to plan realistic solutions, and the ability to construct knowledge by mapping the content of appropriate concepts in learning outcomes. The results showed that contextual constructive learning through virtual learning could develop the creative cognitive process ability of level 1 students in learning citizenship, with a